Chronic Coronary Syndrome with Left Ventricular Apicoseptal Aneurysm - Yudie Tanta; Taufik Indrajaya (Jurnal RSMH Palembang, 2021)
The left ventricular aneurysm is one of the worst complications of acute myocardial infarction episodes. Fibrous tissue replacing dead myocardial cells in an infarcted area can’t perform contraction and herniate outward during systole. In turn, a left ventricle aneurysm will present devastating clinical outcomes such as heart failure, ventricular arrhythmias, even sudden cardiac death. A 65 year-old man came to our hospital complaining of worsened chest pain 5 days before admission, located on the left side of his chest. It was described to have a squeezing character. The symptom was inducted when he doing some mild activities and relieved with a short time rest. He had this symptom for one year. In the past, this symptom was inducted by heavier activities. He also complains of having shortness of breath for the past 2 months, the symptom was also relieved by resting. He had been admitted to the hospital for a heart attack twice before.. He has diabetes and hypertension, thus he consumed metformin 500 mg 3 times a day, and amlodipine 5 mg daily. He also had a history of kidney stone and prostate hypertrophy operation on March 2021. No remarkable abnormality was found in physical examination. On laboratory workup, there was a slight elevation of serum creatinine concentration. The troponin level was in the normal range. ECG and Echocardiography finding supported the ventricular aneurysm as one of the complications of acute myocardial infarction.